A Pediatric Case of Sclerodermatous Graft‐Versus‐Host Disease Responsive to Ultraviolet A1 Phototherapy. Issue 2 (12th February 2016) - Lazzeri, Linda; Tripo, Lara; Pescitelli, Leonardo; Ricceri, Federica; Prignano, Francesca
Abstract: Graft‐versus‐host disease (GVHD) is one of the major complications after hematopoietic stem cell transplantation and is responsible for post‐therapeutic morbidity, mortality, and poor quality of life of recipients. Sclerodermatous graft‐versus‐host disease (sGVHD) is a rare variant of chronic GVHD characterized by deposition of collagen in the skin and other soft tissues and resulting in loss of range of motion and functional capabilities. Treatment of sGVHD is challenging and largely limited by systemic side effects. Ultraviolet A1 phototherapy has been reported to be effective in connective tissue disorders, including sGVHD. We report a case of sGVHD in a 15‐year‐old girl that was resistant to traditional therapy but showed improvement in cutaneous symptoms with ultraviolet A1 phototherapy three times a week for 6 weeks (10 J/cm 2 single dose, 180 J/cm 2 cumulative dose).